Loneliness and older adults: psychological resilience and technology use during the COVID-19 pandemic—a cross sectional study - Balki, Eric; Hayes, Niall; Holland, Carol (Frontiers in Aging, 2023)
This study investigated how psychological resilience influenced greater technology use among older adults, and whether they moderated the impact of social isolation on loneliness during the COVID-19 pandemic. We also explored whether technology mediates the impact of psychological resilience on loneliness. To explain the relationship between variables, the research drew upon the socio-emotional selective theory, which posits the notion that older adults are more focused on current and emotionally important relationships and goals concerning emotional regulation goals such as psychological wellbeing.